Anatomical construction of book covers by indie publishing houses in Yogyakarta - Mawaidi, Mawaidi (Sungging: Journal of Innovative, Cultural, Transdisciplinary Art and Kriya Discourse, 2024)
Changes upon changes in anatomical elements on book covers are common in the publishing industry. However, changes in anatomical elements have always been read as meaningless. This research aims to describe the meaning of changes in the anatomy of book covers in indie publishers in Yogyakarta. This research method uses deconstructive qualitative analysis using book anatomy concepts from experts, including Michael Bhaskar. The results of this study show three patterns of change construction. First is layout construction. This layout-based anatomical change uses a templateable technique that attracts the reader's attention. Second, colour construction: This design pattern was applied to publishers who thought white could be a publication's identity. Third, construction of totality: This last part is a significant finding because of all the anatomical elements used by mainstream publishers; there is one publisher that negates the existence of critical anatomical elements that are not used, namely ISBN.